Animal Models in Studying Cerebral Arteriovenous Malformation. (16th November 2015) - Xu, Ming; Xu, Hongzhi; Qin, Zhiyong
Abstract : Brain arteriovenous malformation (AVM) is an important cause of hemorrhagic stroke. The etiology is largely unknown and the therapeutics are controversial. A review of AVM-associated animal models may be helpful in order to understand the up-to-date knowledge and promote further research about the disease. We searched PubMed till December 31, 2014, with the term "arteriovenous malformation, " limiting results to animals and English language. Publications that described creations of AVM animal models or investigated AVM-related mechanisms and treatments using these models were reviewed. More than 100 articles fulfilling our inclusion criteria were identified, and from them eight different types of the original models were summarized. The backgrounds and procedures of these models, their applications, and research findings were demonstrated. Animal models are useful in studying the pathogenesis of AVM formation, growth, and rupture, as well as in developing and testing new treatments. Creations of preferable models are expected.